(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Interaction is actively carried out not only with the help of methodologically neutral linguistic means but also with the help of figurative, emotional-affective language units. After all, live speech is by nature full of colorful artistic-visual means, figurative linguistic units, and words and phrases expressing hysteria, which create the language of artistic monument attractiveness, expressiveness, folklore, and national character.